ANALISIS KESALAHAN DIKSI DAN GAYA BAHASA PIDATO PEJABAT PEMERINTAHAN BERKAITAN DENGAN PANDEMI COVID-19 - Eli Syarifah Aeni; Yusep Ahmadi F (STKIP Siliwangi, 2021)
The emergence of the Covid-19 pandemic caused many officials to make speeches regarding the Covid-19 outbreak. The speech was in the form of reports, appeals, and support for health protocol policies during the Covid-19 pandemic. The analysis of errors in the use of diction and the use of governmental language styles is interesting to analyze and can be used as online teaching materials in the language error analysis course. The purpose of this study is to describe the patterns of diction errors and to describe the style of speech of government officials regarding Covid-19. This study uses a qualitative descriptive method that describes language data in speeches of government officials regarding Covid-19. The data analysis technique used the language error analysis approach (diction) and the language style analysis approach. Collecting data in research using observation techniques and note-taking techniques. The data source comes from speeches by government officials regarding Covid-19. The results of the study show that there are still many uses of wrong and inaccurate diction, the use of conjunctions from, but, the use of prepositions in and in the wrong, the form / pronunciation of the day and the date, and there are still many jumbo word uses. Meanwhile, the language styles found included parallelism, climax, anticlimax, association, pleonasm and repetition.